Different Aspects of Mobility and Migration During the Middle Kingdom - Priglinger, Elisa (Ägypten und Levante, 2020)
For quite some time it has been assumed that during the Middle Kingdom there was a strong immigration from the Near East to Egypt. The explanatory models are based on many different concepts without being explicitly explained in most cases. This paper examines the question of migration in the early second millennium BCE by addressing existing cultural concepts and associating them with various aspects of mobility. For this consideration it is indispensable to work out and question the meaning of ethnicity and group identity, especially with regard to the period following the Middle Kingdom and the rule of the Hyksos in Egypt.